Phenomenological Study: Spiritual Experiences of HIV/AIDS Patients at Waluyojati Hospital - Nugroho, Setiyo Adi; Lutfiatul Muslimah, Lutfiatul (Fakultas Kesehatan, Universitas Nurul Jadid, 2024)
Introduction: The issues faced by HIV/AIDS patients are not only psychological but also spiritual, such as their relationship with others, themselves, and God. The negative labels received by HIV/AIDS patients can sometimes lead them to blame God for the trials they face, as each individual has different levels of spirituality. Objectives:The purpose of this research is to understand the spiritual experiences of HIV/AIDS clients at Waluyo Jati Regional Hospital, Kraksaan Probolinggo. Methods: This study employs a qualitative research method with a phenomenological approach, using data collection techniques such as observation, interviews, and documentation. The number of informants in this study is five people, who have reached saturation. Results: The results of the study show that the spiritual experiences of HIV/AIDS clients involve drawing closer to God by praying and spending their free time reciting the Quran. However, in their relationships with others, HIV/AIDS clients keep their illness a secret because they fear being shunned by those around them, and they even hide it from their families. Conclusions: Therefore, further research is needed to address the social issues faced by HIV/AIDS patients.